Pengembangan Flipped Classroom dengan Pendekatan Saintifik untuk Meningkatkan Pemahaman dan Keterampilan Menulis Teks Deskripsi Siswa Kelas V - Nurul Kholifah; Mustaji Mustaji; M. Turhan Yani (UNIB Press, 2022)
This study aims to investigate the validity, practicality, and effectiveness of developing flipped classroom with a Scientific Approach to improve students' understanding and skills in writing the descriptive text for the fifth graders of SDN Pucang 1 Sidoarjo. This study used DDD-E model by Ivers & Barron. The data collected were documentation, validation, observation, questionnaire, and test. The data analysis was done using a quantitative method from the analysis of observation data and teachers’ and students’ questionnaires. The result of this study showed (1) high validity of flipped classroom model in creating a lesson plan, students’ worksheet, attitude and skills assessment sheet and study result test. (2) The practicality of the flipped classroom model in accordance with student responses and the implementation of the lesson plan was declared to receive a positive response from the students and the lesson plan was well-implemented. (3) The effectiveness of the flipped classroom model with a scientific approach to improving students’ understanding and writing skills of descriptive text. In the field trial the t-statistic = 26,889 > t-table = 2,042 which means that there is a significant difference between X1 and X2. Based on these results, it was concluded that the understanding and writing skills of the fifth-grade students were improved after using the flipped classroom model with a scientific approach.